Recursos hídricos: percepção ambiental de agricultores e estudo dos efeitos ecotoxicológicos da água do Rio Piancó e de metais pesados em espécies agrícolas - Oliveira, José Lucas dos Santos (2019)
The antropic actions related to the intense natural resources exploration and the populational increase has contributed to an environmental crisis, resulting in imbalances and contamination in aquatic and soil ecosystems. This research aimed to analyze the knowledge and practices of farmers regarding water resources and sustainable land use. In addition, to evaluate the possible ecotoxicological effects of Piancó river (Paraiba) water and metals (Ni, Pb) in the germination development of three cultivars: Citrulus lanatus (watermelon), Phaseolus vulgaris L. (bean), Zea mays L. (corn) as well as possible genotoxic effects of the river water on Allium cepa (onion). A questionnaire with 5 open questions and 12 affirmative questions in the Likert scale model, all related to their relation and their activities with the use of river water and soil, were applied in the field survey with farmer’s families (n = 8) in the city of Pombal, Paraiba. Laboratory experiments were carried out in Petri dishes with 25 seeds in each plate. For the experiments with the water of the river, the water was collected in two sampling points close to the contamination sources (effluents) of the river. The samples were characterized according to chemical physical parameters (pH, color, turbidity, total dissolved solids, temperature, electrical conductivity, dissolved oxygen, biochemical oxygen demand, chemical oxygen demand, total hardness, sodium, potassium, calcium, bicarbonate and chlorides). The ecotoxicological effects of the river water were evaluated at different dilutions (100,0; 75,0; 50,0; 25,0 and 0,0%) by volume of water, for each sampling point using the species C. lanatus, P. vulgaris and Z. mays. The effects of metals (Ni, Pb) were evaluated in the following concentrations: 0,0; 1,0; 3,0; 6,0 and 9,0 mM in C. lanatus. The morphophysiological responses observed were: percentage of germination, abnormalities, fresh and dry root and shoot biomass, germination speed index (IVG), mean germination time (TMG), root and shoot growth. The genotoxicity was evaluated by the analysis of meristematic cells of A. cepa exposed to the water of the river. The data reported that the water of the Piancó River is important for the region because farmers derive their subsistence from it. The interviewees understand that urbanization compromises the quality of the river's water (62,5%) and knows which agency is responsible for monitoring the river (50,0%). Only 25,0% use natural pesticides in the crops. The others use agrochemicals. The chemical physical parameters of the Piancó River water are, for the most part, according to the brazilian legislation for this class of use, in the two sampling points did not report toxicity in P. vulgaris in the evaluated variables, but C. lanatus had a reduction of IVG in the two points and Z. mays had a significant reduction of growth and biomass production when exposed to concentrated water from the river at one of the collection points. The heavy metals analyzed were toxic to germination and development of C. lanatus, from 1,0 mM, with Pb being more toxic than Ni. Effluents and leached water from agriculture can accumulate in the water and subsequently in the soil (through irrigation) of toxic heavy metals. Therefore, for the practice of agriculture around the perimeter that borders the Piancó River, conservation actions are necessary to mitigate the effects of anthropic activities and releases of effluents that contribute to the degradation of the river. Environmental Education actions can sensitize farmers to contribute to the preservation of the area, reducing the use of pesticides or being trained in agroecological practices.